STRUCTURAL AND FUNCTIONAL CHANGES IN OSTEOGENIC CELLS AND BIOMARKERS OF BONE REMODELING IN CHRONIC HYPERGLYCEMIA - Ponyrko, Alina; Bumeister, Valentyna; Korenkov, Oleksiy; Dmytruk, Serhiy; Kiptenko, Liudmyla; Ryabenko, Tetiana; Teslyk, Tetiana; Ryabenko, Dmytro (Eastern Ukrainian Medical Journal, 2023)
Analysis of the results of experimental studies on skeletal bone structure disorders in the setting of hyperglycemia discovered a lack of information on the peculiarities of the remodeling process and structural and functional changes of osteogenic cells in long tubular bones depending on the duration of diabetes mellitus.Objective. Therefore, the aim of our experimental study was to determine the peculiarities of the effect of hyperglycemia on bone remodeling and structural and functional changes in osteogenic cells of long tubular bones of mature rats.Methods and Materials. Methods used to study the structure of femurs: 1) transmission electron microscopy, 2) immunohistochemical examination. In the study of osteoblasts, special attention was paid to the integrity of cellular structures and membrane organelles, the presence of cytoplasmic vacuolization.Results. Analysis of the osteogenic activity in the bone tissue of the experimental group showed that an increase in blood glucose leads to a change in the concentration of osteopontin, which directly affects the formation of bone tissue. The immunohistochemical study of osteogenic cells revealed a significant disruption of the structure of organelles, which leads to a disruption of the normal functioning of these cells, which is manifested in a decrease in osteopontin levels and a gradual increase in RANKL.Conclusions. It can be noted that under hyperglycemia conditions, structural disorders of osteoblasts occur already on the 30th day of the experiment: significant hypertrophy of the granular endoplasmic reticulum (GER), increasing destruction of membrane organelles with further progression in accordance with the increase in the duration of chronic hyperglycemia.